PENGARUH ALOKASI DANA DESA TERHADAP KUALITAS DAERAH TERTINGGAL - Marihot Nasution; Ade Nurul Aida (Pusat Kajian Anggaran, 2018)
The regional autonomy realized in the allocation of village funds has not been able to reduce the existing inequality in Indonesia, especially if it concerns the disadvantaged areas. This study examines the impact of village funds on the economic condition of the community; quality of human resources; and local financial capacity for three years the enactment of village funds for disadvantaged areas. The results show that the village funds have no impact on the economic condition of the community, quality of human resources, and regional financial capacity in disadvantages areas. This can happen if the community empowerment is still weak. As long as the village funds are in place, the focus of the village is still on improving infrastructure development, not on community empowerment, if done, will have an impact on increasing the economic level of the community. This condition occurs even though in the mandate of legislation has been mentioned that the focus of village funds is not only on infrastructure development but also community empowerment. Balancing the utilization of village funds by the villages themselves need to be enforced, because the development of infrastructure without empowerment will have an impact on the higher inequality in the village itself.